Teacher Training Workshops on Black English and Language Arts Teaching - Lewis, Shirley A. R.; Hoover, Mary R.; Stanford Univ., CA. Center for Educational Research at Stanford ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1979)
This booklet outlines the content and activities of two workshops aimed at improving the teaching of children who speak Black English. Its goals are to supplement research reports on test development in the area of Black English and to serve as a useful starting point for those who rely on the workshop format to inform teachers about Black English and dialect variation. The first workshop outlined acquaints teachers with the development and characteristics of varieties of Black English and discusses procedures for administering and interpreting tests of students' oral language competence in one or more speech varieties. The second workshop outlined concentrates on varying communication styles, black community attitudes toward the use of different Black English speech varieties, and the characteristics of schools where black pupils perform successfully. (RL)
Sponsoring Agency: National Inst. of Education (DHEW), Washington, DC.
Sponsoring Agency: Office of Education (DHEW), Washington, DC.
Contract Number: OB-NIE-G-0112.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Black Dialects; English Education; Language Attitudes; Language Styles; Language Variation; North American English; Teacher Attitudes; Teacher Education; Teacher Workshops; Reports, Descriptive